Dose-banding of intravenous piperacillin-tazobactam in pediatric surgical inpatients - Karande, I.; Goff, Z.; Kewley, J.; Mehta, S.; Snelling, Thomas (2017)
© Published by the Pediatric Pharmacy Advocacy Group. All rights reserved. BACKGROUND Antimicrobial doses in children are often prescribed by using an individually calculated dose per weight (e.g., mg/kg) or based on body surface area. Dosing errors are the most commonly reported medication errors in children. A “dose-banding” strategy is frequently used for some over-the-counter drugs to prevent dosing errors. It could also lead to efficiencies by enabling batch preparation of intravenous (IV) medications in hospitals. OBJECTIVES To evaluate whether use of dose-banding for IV piperacillin-tazobactam results in acceptable dose variation from standard practice of individualized prescription of 100 mg/kg in children. METHODS We conducted a historically controlled intervention study comparing prescriptions of IV piperacillin-tazobactam before vs. after introduction of dose-banding prescribing guidance for surgical inpatients weighing > 5 kg and < 16 years of age at the tertiary referral pediatric hospital in Western Australia. RESULTS Dose-banding of IV piperacillin-tazobactam (with a maximum of 15% departure from the recommended milligram-per-weight dose of 100 mg/kg) resulted in similar overall variation of prescribed dose in comparison to individualized milligram-per-weight (non-dose-banded) prescribing. There was a trend toward fewer prescriptions with large variance ( > 30% variation from the 100-mg/kg dose) in the dose-banded compared to the non-dose-banded group (1/140 vs. 5/105; p = 0.09). CONCLUSIONS Our study showed dose-banding of IV piperacillin-tazobactam resulted in acceptable variation when compared to individualized milligram-per-weight dosing in children. Prospectively designed controlled trials are warranted to determine whether dose-banding could reduce medication errors and optimize use of hospital resources. Implications for future practice could include faster batch preparation, shorter checking and dispensing time, and reduction in drug wastage.